Ocena vplivov na zdravje, zgodovinski okvir in osnove metodologij - Gabrijelčič Blenkuš, Mojca (Zdravstveno varstvo, 2004)
The importance of public health has been recognised almost century ago in Slovenia. Long tradition in this field and regular updating with trends in Europe and worldwide has helped public health sector to follow new developmentin health impact assessment accurately Impacts on human health arenot limited to specific health policies, health is a theme that cuts acrossall sectors. That why health impact assesmet was introduced as a new tool which enables informed policy decisions to be made based on a valid assessment of their potential health impacts.
Keywords: javno zdravje; preventivna medicina; zdravje